Adjuvant Therapy of Pancreatic Cancer - Chaulagain, Chakra P; Ng, John; Goodman, Martin D; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Abstract: There is no clear consensus on what type of adjuvant therapy should be used for patients with pancreatic cancer. Chemoradiation is the favored treatment modality by many in the United States while gemcitabine based chemotherapy is favored in Europe. Both of these approaches have been shown by large prospective, randomized trials to improve disease free intervals and in some studies overall survival. This review is an update from the 2013 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancer Symposium held in San Francisco, CA, USA. We present the summary of the findings from Abstracts #145 and #269 and discuss the potential impact on our clinical practice on this highly lethal cancer. Image: Sign (Tufts Medical Center. Boston, MA, USA).